Molecular identification of Candida albicans and Candida dubliniensis strains isolated from clinical samples - Aşçi Toraman, Zülal; Bulut, Yasemin; Yilmaz, Mustafa; Özdarendeli, Aykut (My University, 2005)
Candida dubliniensis is a recently identified opportunistic pathogen, which has close phylogenetic relation with Candida albicans. The aim of this study was the genotypic differentiation of 55 germ tube-positive Candida strains isolated from clinical specimens (30 blood, 25 throat swab specimens). The isolates were phenotypically identified by API ID 32C system, and genotypically identified by using polymerase chain reaction-restriction fragment lenght polymorphism (PCR-RFLP) method. Initially ITS2 region has been amplified by using universal fungal primers with PCR. After amplification and purification of approximately 340 base pair products, they were treated with species-specific restriction enzymes (MspA1 I and BsmAl for C.albicans and C.dubliniensis, respectively). As a result, API ID 32C system identified 52 (94.5%) isolates as C.albicans and 3 (5.5%) isolates as C.dubliniensis, whereas PCR-RFLP analysis yielded 50 (90.9%) C.albicans and 5 (9.1%) C.dubliniensis. It can be concluded that PCR-RFLP method may be used for the differentiation of C.dubliniensis and C.albicans isolates in clinical samples.
Klinik örneklerden izole edilen Candida albicans ve Candida dubliniensis suşlarinin moleküler olarak tanimalnmasi
Keywords: Candida albicans; Candida dubliniensis; Genotypic identification; Polymerase chain reaction